Negative feedback via RSK modulates Erk‐dependent progression from naïve pluripotency. (12th June 2018) - Nett, Isabelle RE; Mulas, Carla; Gatto, Laurent; Lilley, Kathryn S; Smith, Austin
Abstract: Mitogen‐activated protein kinase (MAPK)/extracellular signal‐regulated kinase (ERK) signalling is implicated in initiation of embryonic stem (ES) cell differentiation. The pathway is subject to complex feedback regulation. Here, we examined the ERK‐responsive phosphoproteome in ES cells and identified the negative regulator RSK1 as a prominent target. We used CRISPR/Cas9 to create combinatorial mutations in RSK family genes. Genotypes that included homozygous null mutations in Rps6ka1, encoding RSK1, resulted in elevated ERK phosphorylation. These RSK‐depleted ES cells exhibit altered kinetics of transition into differentiation, with accelerated downregulation of naïve pluripotency factors, precocious expression of transitional epiblast markers and early onset of lineage specification. We further show that chemical inhibition of RSK increases ERK phosphorylation and expedites ES cell transition without compromising multilineage potential. These findings demonstrate that the ERK activation profile influences the dynamics of pluripotency progression and highlight the role of signalling feedback in temporal control of cell state transitions. Synopsis: MAPK/ERK signalling promotes ES cell differentiation. Negative feedback on ERK1/2 signalling influences the rate at which ES cells exit from naïve pluripotency. Interference with feedback regulator RSK increases the speed and homogeneity of transition to differentiation. Negative regulator RSK1 is a major target of ERK signalling in ES cells. RSK feedback restricts ERK activation and constrains exit from naïve pluripotency. Genetic depletion of RSKs accelerates ES cell differentiation. Chemical inhibition of RSKs increases the rate and uniformity of ES cell transition. Abstract : MAPK/ERK signalling promotes ES cell differentiation. Negative feedback on ERK1/2 signalling influences the rate at which ES cells exit from naïve pluripotency. Interference with feedback regulator RSK increases the speed and homogeneity of transition to differentiation.